Claiming Nobility in the Monarquía Hispánica: The Search for Status by Inca, Aztec, and Nasrid Descendants at the Habsburg Court - Cook, Karoline P. (Renaissance and Reformation / Renaissance et Réforme, 2020)
By the early seventeenth century, petitioners at the royal court in Madrid who claimed descent from the Inca rulers of Peru, the Aztec rulers of Mexico, and the Nasrid emirs of Granada found ways to acquire noble status and secure rights to their ancestral lands in the form of entailed estates. Their success in securing noble status and title to their mayorazgos (entailed estates) rested on strategies, used over the course of several generations, that included marriages with the peninsular nobility, ties of godparentage and patronage, and military service to the crown. This article will examine the networks formed in Madrid between roughly 1600 and 1630 when the descendants of the Inca and Aztec rulers interacted with peninsular noble families at court, obtaining noble status and entry into the military orders and establishing their mayorazgos. Their strategies for claiming nobility show striking parallels to those adopted by the Morisco nobility, and one aim of this article is to suggest how knowledge of such strategies circulated among families both at the royal court in Madrid and in the viceroyalties of New Spain and Peru.